Outer Membrane Vesicles Released From Aeromonas Strains Are Involved in the Biofilm Formation - Seike, Soshi; Kobayashi, Hidetomo; Ueda, Mitsunobu; Takahashi, Eizo; Okamoto, Keinosuke; Yamanaka, Hiroyasu (Frontiers in Microbiology, 2021)
Aeromonas spp. are Gram-negative rod-shaped bacteria ubiquitously distributed in diverse water sources. Several Aeromonas spp. are known as human and fish pathogens. Recently, attention has been focused on the relationship between bacterial biofilm formation and pathogenicity or drug resistance. However, there have been few reports on biofilm formation by Aeromonas. This study is the first to examine the in vitro formation and components of the biofilm of several Aeromonas clinical and environmental strains. A biofilm formation assay using 1% crystal violet on a polystyrene plate revealed that most Aeromonas strains used in this study formed biofilms but one strain did not. Analysis of the basic components contained in the biofilms formed by Aeromonas strains confirmed that they contained polysaccharides, extracellular nucleic acids, and proteins, as previously reported for the biofilms of other bacterial species. Among these components, we focused on several proteins fractionated by SDS-PAGE and determined their amino acid sequences. The results showed that some proteins existing in the Aeromonas biofilms have amino acid sequences homologous to functional proteins present in the outer membrane of Gram-negative bacteria. This result suggests that outer membrane components may affect the biofilm formation of Aeromonas strains. It is known that Gram-negative bacteria often release extracellular membrane vesicles from the outer membrane, so we think that the outer membrane-derived proteins found in the Aeromonas biofilms may be derived from such membrane vesicles. To examine this idea, we next investigated the ability of Aeromonas strains to form outer membrane vesicles (OMVs). Electromicroscopic analysis revealed that most Aeromonas strains released OMVs outside the cells. Finally, we purified OMVs from the Aeromonas 104 strain and examined their effect on the biofilm formation. We found that the addition of OMVs dose-dependently promoted biofilm formation. These results suggest that the OMVs released from the bacterial cells are closely related to the biofilm formation of Aeromonas strains.